1996
DOI: 10.3171/jns.1996.85.2.0221
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical suitability of the C1–2 complex for transarticular screw fixation

Abstract: Posterior transarticular screw fixation of the C1-2 complex has become an accepted method of rigid internal fixation for patients requiring posterior C1-2 fusion. The principal limitation of this procedure is the location of the vertebral artery, because an anomalous position may prohibit screw placement. In this study, a consecutive series of computerized tomography (CT) scans was reviewed, and the suitability of each patient for transarticular screw fixation was evaluated. All of the fine-slice axial C1-2 CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
179
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(191 citation statements)
references
References 7 publications
3
179
0
7
Order By: Relevance
“…Placement of either C1-C2 transarticular or C2 pedicle screws has a potential risk of vertebral artery injury [1][2][3][4][5][6][7][8][9][10][11][12][13][14]21]. The risk of vertebral artery injury by these two techniques needs to be carefully analyzed so as to allow the surgeon to choose the appropriate screw insertion method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Placement of either C1-C2 transarticular or C2 pedicle screws has a potential risk of vertebral artery injury [1][2][3][4][5][6][7][8][9][10][11][12][13][14]21]. The risk of vertebral artery injury by these two techniques needs to be carefully analyzed so as to allow the surgeon to choose the appropriate screw insertion method.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral artery injuries commonly occur if a drill, tap, or screw perforates or occludes the vertebral artery in the vertebral artery groove of C2, which is located on the lower surface of C2 and lateral to the pedicle ( Fig. 1) [1][2][3][4][5][6][7][8]. It has been suggested that C2 pedicle screw combined with C1 lateral mass screw placement is inherently safer than C1-C2 transarticular screw fixation in view of the risk of vertebral artery injury at C2, as the medially directed trajectory of the C2 pedicle screw carries the screw away from the vertebral artery, which normally is located lateral to the screw [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the vertebral arteries have to have a particular anatomy to allow safe placement of C1-2 transarticular screws. If the artery has an unusual course, as has been shown to occur in 10-20% of adult patients, then a screw can not safely be placed on that side [26,31,32,37]. In one study on pediatric patients, the authors found that the anatomy of the vertebral artery prevented safe placement of a transarticular screw in 11% of joint spaces [6].…”
Section: Discussionmentioning
confidence: 99%
“…El trayecto de la arteria vertebral a este nivel es, por lo tanto, variable en forma, tamaño, localización y simetría. Estudios radiológicos y en cadáveres sugieren que existe una anatomía desfavorable para la colocación de estos tornillos, por lo menos en un lado, en el 18-23% de los casos debido al trayecto de la arteria vertebral 1,10,14,18 . En concreto, se ha estimado el riesgo de lesión de la arteria vertebral durante la inserción de los tornillos trasarticulares C1-C2 en 4-8% 10,14,24,25 .…”
Section: Discussionunclassified